Investigating the Strategies Employed by Fast-Food Restaurant to Establish Sustainable Customer Relationships - Kok Ban Teoh; Jia Lin Jocelyne Lee; Rudkouskaya Volha; Muhammad Syazwan Afifi Bin Zamri; Nadiah Hidayah Binti Azian; Pei Long Ng; Zulkifli Ega Irvan Maulana; Seviana Via; Gerasimenko Vladimir; Daisy Mui Hung Kee (International Journal of Tourism and Hospitality in Asia Pasific, 2024)
McDonald’s Corporation, established in 1940, is an American multinational fast-food chain. Over the years, McDonald’s has successfully expanded their business operation worldwide. The customer plays a vital role in the success of a business. The strategies and abilities to retain a customer will determine the survival of a business. Hence, this study aims to investigate the strategies employed by McDonald's to foster long-term customer relationships by examining various factors, including food quality, service quality, atmosphere, price, brand, and customer relationships. To explore, primary and secondary data collection was conducted through several sources, and a digital questionnaire was produced to collect data and information from 150 respondents. The results found that only atmosphere and brand had a significant positive impact on customer relationships. The study found that atmosphere has the strongest influence, followed by brand. This suggests that while food quality, service quality, and price are important, creating a pleasant atmosphere and fostering a strong brand are even more critical for McDonald's to build lasting customer relationships.